Characterisation and properties of polyisoprene (IR)/polybutadiene (BR) rubber blends-reinforced silanised silica nano-filler - Rehman, A; Saeed, F; Shuib, R K (Journal of Rubber Research, 25(3): 223-230., 2022)
Synthetic polyisoprene (IR) rubber and polybutadiene (BR) rubber were mixed together to produce three IR/BR blends. The loading of BR in the blends was varied from 10 to 30 phr. Silanised silica was used as a nano-filler as well as vulcanising filler to reinforce and crosslink the rubber simultaneously. The crosslinking in the rubber was achieved by activating the tetrasulfide group of silane bis[3-triethoxysilylpropyl]-tetrasulphide (TESPT) using a non-sulphur donor accelerator and zinc oxide as an activator. The hardness, tensile strength, elongation at break, stored energy density at break, modulus at 100% elongation (M100), crosslink density and abrasion resistance of the blends were measured. The increasing loading of BR had a detrimental effect on the hardness, tensile strength, elongation at break and M100 of the blends. On the other hand, the abrasion resistance and thermal stability of the blends improved with the loading of BR. The blend with 20 phr BR loading was selected as the optimum blend for better abrasion resistance and mechanical properties. The 80/20 (IR/BR) blend can be used for potential light truck tyre tread compounds.
Keywords: Polyisoprene; Polybutadiene; Blends; Silica; Silane; Mechanical properties; Abrasion